Faktor – faktor yang berhubungan dengan kejadian anemia pada anak usia 6-59 bulan di RSUD Wangaya, Denpasar, Bali, Indonesia tahun 2019 - Elien Yuwono; I Wayan Bikin Suryawan; Anak Agung Made Sucipta (DiscoverSys Inc., 2020)
Background: Anemia is one of the four micronutrient problems in Indonesia. Based on Global Prevalence on Anemia, the Southeast Asian region is one of the areas with the highest prevalence of anemic populations, more than 53.8% of children aged 6-59 months were classified as mild anemia, and 3.6% of them are severe anemia. In the first 1000 day birth gold period, anemia was associated with delays and developmental disorders, both motor and intellectual, which may be irreversible. This study aims to analyze the risk factors for the incidence of anemia to optimize child development.Objective: To analyze the relations of the risk of age under two years old, low birth weight, underweight, short stunting, and not exclusive breastfeeding, to the incidence of anemia in children aged 6-59 months in Kaswari Room, Wangaya General Hospital, Denpasar in 2019.Methods: Observational analytic epidemiology design with case-control study. The research subjects were determined by consecutive sampling method and fulfilled the inclusion criteria with a comparison of case and control groups, namely 1: 1. Data were analyzed bivariate by chi-square statistical test and Odds Ratio (OR) at the significance limit of α=5%, and multivariate analysis was performed with logistic regression test. Data was processed using the Statistical Package for Social Science (SPSS) version 23 for Windows program.Results: The research subjects were 62 samples, consisting of 31 anemia samples, and 31 samples had no anemia. The results showed that there was no significant relationship between the risk of low birth weight and the incidence of anemia (95% CI = 0.80 - 22.29; p: 0.073), the risk of malnutrition with the incidence of anemia (95% CI = 0.81 - 63.85; p: 0.052), and the risk of not exclusive breastfeeding with the incidence of anemia (95% CI = 0.21 - 1.63; p: 0.440). However, there was a significant relationship between the risk of age <2 years with the incidence of anemia (OR 3.870; 95% CI = 1.34 - 11.17; p: 0.022) and the risk of short stature with the incidence of anemia (OR 7.686; 95% CI = 1, 92 - 30.70; p: 0.002). Logistic regression test results obtained significant results in short stature variables (sig 0.020; OR 5.379).Conclusion: age <2 years and short stature (stunting) have a significant relationship with the incidence of anemia in children aged 6-59 months in Kaswari Room, Wangaya Hospital, Denpasar in 2019. Latar belakang : Anemia merupakan salah satu dari empat masalah gizi mikro masyarakat Indonesia. Berdasarkan Global Prevalence on Anaemia, regio Asia Tenggara menjadi salah satu kawasan dengan prevalensi tertinggi populasi anemia, lebih dari 53,8% anak usia 6-59 bulan diklasifikasikan anemia ringan, serta 3,6% di antaranya adalah anemia berat1. Pada periode emas 1000 HPK, anemia berhubungan dengan keterlambatan dan gangguan perkembangan baik motorik maupun intelektual yang mungkin irreversible2. Penelitian ini bertujuan untuk menganalisis faktor-faktor risiko kejadian anemia sebagai langkah mengoptimalkan tumbuh kembang anak.Tujuan : Menganalisis hubungan risiko usia < 2 tahun, berat badan lahir rendah, gizi kurang (underweight), perawakan pendek (stunting), dan tidak ASI eksklusif, terhadap kejadian anemia pada anak usia 6-59 bulan di Ruang Kaswari, RSUD Wangaya, Denpasar tahun 2019.Metode : Rancangan epidemiologi analitik observasional dengan desain studi case control. Subyek penelitian ditentukan dengan metode consecutive sampling, serta memenuhi kriteria inklusi dengan perbandingan kelompok kasus dan kontrol yaitu 1:1. Data dianalisis bivariat dengan uji statistic chi-square dan Odds Ratio (OR) pada batas kemaknaan α 5%, serta dilakukan analisis multivariat dengan uji regresi logistic. Data diproses menggunakan program Statistical Package for Social Science (SPSS) versi 23 for Windows.Hasil : Subjek penelitian sejumlah 62 sampel, terdiri dari 31 sampel anemia dan 31 sampel tidak anemia. Hasil penelitian menunjukkan bahwa tidak didapatkan hubungan bermakna antara risiko berat badan lahir rendah dengan kejadian anemia (95% CI = 0,80 – 22,29; p:0,073), risiko gizi kurang dengan kejadian anemia (95% CI = 0,81 – 63,85; p:0,052), serta risiko tidak ASI eksklusif dengan kejadian anemia (95% CI = 0,21 – 1,63; p:0,440). Namun didapatkan hubungan bermakna antara risiko usia < 2 tahun dengan kejadian anemia (OR 3,870; 95% CI = 1,34 – 11,17; p:0,022) dan risiko perawakan pendek dengan kejadian anemia (OR 7,686; 95% CI = 1,92 – 30,70; p:0,002). Hasil uji regresi logistic, didapatkan hasil bermakna pada variabel perawakan pendek (sig 0,020; OR 5,379).Kesimpulan: usia < 2 tahun dan perawakan pendek (stunting) memiliki hubungan bermakna dengan kejadian anemia pada anak usia 6-59 bulan di Ruang Kaswari, RSUD Wangaya, Denpasar tahun 2019.